Agribusiness Indicators : Ghana - World Bank (Washington, DC, 2013)
Agriculture plays an important role in the economies of most countries in Africa. However, few African countries have been able to capitalize on the sector's considerable potential to contribute to economic development through commercialization. Few have created an enabling environment for agricultural finance in which lenders and other agents are encouraged to develop innovative financial products that are well tailored to meet the needs of local producers. Few African countries have purposefully set out to encourage the use of modern farm machinery. Some, however, have invested in road infrastructure and transport facilities to reduce transaction costs and improve producers' access to markets. The countries that have undertaken initiatives to expand producers' access to agricultural technologies such as certified or hybrid seeds and fertilizers have generally been the most effective at increasing agricultural productivity. The research described in this volume used a set of agribusiness indicators to collect data that capture the performance of the agriculture sector in the Republic of Ghana, using a list of preliminary indicators covering the following areas: (i) access to and availability of certified seed; (ii) availability of and access to fertilizer; (iii) access to farm machinery, particularly tractor hire services for land preparation; (iv) access to agricultural and agro-enterprise finance; (v) cost and efficiency of transport; (vi) measures of policy certainty and the orientation of the enabling environment as perceived by the private sector; and (vii) various policy, trade, and fiscal measures. Ghana was the first country in which these indicators were tested for ease and consistency. The indicators were then finalized and used for data collection in two other African countries (Ethiopia and Mozambique).